BODY IMAGE DAN KECEMASAN SOSIAL PADA REMAJA PEREMPUAN DI KOTA MAKASSAR - Muhammad Nur Iksan M; Ahmad Razak; Nurfitriany Fakhri (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to determine the relationship between body image and social anxiety in adolescent girls in Makassar City. Respondents in this study were 355 women aged 17-22 years who live in Makassar City. The sampling technique used is accidental sampling. The measuring instrument used for body image is the MBRSQ-AS scale (a=0,815) and social anxiety on the SAS-A scale (a=0,916). The data analysis process used the Spearman Rho technique with a correlation coefficient of -0.133 with p = 0.012 (p 0.05). These results indicate that there is a negative relationship between the body image variable and the social anxiety of adolescent girls in Makassar City. This means that the lower the body image, the higher the social level as well as the higher the body image, the lower the social anxiety of adolescent girls in Makassar City.